Implementasi Literasi Sekolah melalui Gerakan 15 Menit Membaca dan Pembuatan Poster dalam Meningkatkan Percepatan Membaca di MI Nurul Mun’im Karanganyar Paiton Probolinggo - BZ, Zakiyah; Komariyah, Eni; Nurul Hidayah, Dewi; Astutik, Astutik (Al-DYAS, 2024)
This service aims to describe the implementation of the Reading Literacy Movement in Increasing Reading Acceleration at MI Nurul Mun'im. Based on the problems at MI Nurul Mun'im, there are still some students who are not fluent in reading and have difficulty understanding the material. This research is a qualitative descriptive research, the research subject is the deputy head of facilities and infrastructure, and one of the students in class III IV V VI. The techniques used in data collection are interviews, field observations, documentation, and active participation. The collected data was analyzed using interactive analysis. The implementation of the reading literacy movement in the field is carried out for one hour per class in turns, and the implementation time is 20 days. Reading books are provided in each class or use textbooks studied that day, to monitor student progress in the accelerated reading program. Based on data analysis, it can be concluded that the reading literacy movement was implemented this year and has started to run well. Some students who are still not fluent in reading and have difficulty understanding the material are slowly starting to make progress.